Implementation of International Norms in Russia: The Case of Higher Education - A. Crowley-Vigneau; A. A. Baykov; Ye. Kalyuzhnova (Высшее образование в России)
This article analyses the reasons why Russia adopts foreign norms in the sphere of higher education, looking at how isomorphism, Transnational Advocacy Networks and the global market for education have brought about the country’s integration in the global network of universities. It investigates how Russia strives to adopt international and western educational norms by adhering to the Bologna process and launching projects such as 5-100 to reinforce the competitiveness of its universities on the global stage, but remains concerned about security and national identity issues. These fears have resulted in the government prioritizing the adherence to formal criteria while preserving the historical content of its higher education, thus leading to a dichotomy between substance and structure. This mismatch between the organization of higher education and its content leads to an ineffective implementation of international norms but also to significant disruptions in the existing system. Attempts to levy the advantages of both systems have had opposite results. Indeed, the risks of sudden change are multifold: the sudden “catch-up” mode leads to resistance and to a decline in the overall quality of education in those universities lacking the institutions to support the fast tempo of change. The authors outline the benefits of an incremental adaptation to the international higher education system and the need to adjust international norms to local conditions, by building off the assets of the country’s Soviet heritage. The benefits of involving Transnational Experience and Experience Networks in the implementation of international norms are also reviewed.